Ayurvedic management of pituitary macroadenoma-a case report - Vasanth, Anuja K.; Giri, P. V.; Marikutty, T. C. (International Journal of Research in Medical Sciences, 2024)
Pituitary macroadenoma is an infrequently encountered clinical condition, characterized by a non-metastasizing neoplasm situated within the pituitary gland. This case report endeavours to elucidate the efficacy of ayurvedic interventions in achieving symptomatic resolution. A 44-year-old female patient, residing in Thrissur, diagnosed with features suggestive of pituitary macroadenoma, sought admission to Vaidyaratnam ayurveda college hospital for complaints of generalized pain, heaviness of head, impaired peripheral vision in the left eye, and amenorrhea persisting for approximately 7 months. The case was conclusively diagnosed as Pituitary Macroadenoma and meticulously addressed through therapeutic modalities including takradhara, nasyam, and thalapothichil. patient was already prescribed with Caberlin tablets at a dosage of 0.25 mg twice weekly, administered nocturnally. Following 21 days of treatment, notable improvement in the LBNQ-Pituitary score was observed from 60 to 21 accompanied by significant symptomatic alleviation. A specific treatment protocol for the management of pituitary macroadenoma is currently unavailable.